E-Learning en Endesa: estudio de caso - Jáuregui Machuca, Kety (2003)
In view of the evident potential shown by new technologies for education more and more companies are developing and implementing training programs using the facilities provided by these technologies. In turn new providers have emerged that develop training programs based on these new technologies seeking greater efficiency and lower costs compared to traditional training. The objective of this work is to identify the relevant factors for the success of the training programs with technological support starting from the case of a Spanish company analysed in depth. These factors have been articulated in a conceptual model that respects some theoretical proposals made previously and with which fits reasonably well.